(untitled) (Global Journal of Science Frontier Research, 2023)
Plant establishment depends on the ability of seeds and seedlings to adapt to adverse environmental conditions Thus the objective of this study was to evaluate the influence of the increase in air temperature with variations throughout the day on emergence and initial growth of sorghum cultivars Sorghum bicolor L Moench The experiment was conducted in growth chambers in a 7x3 factorial scheme with a completely randomized design using seven sorghum cultivars AGRI 002E BRS 506 BRS 716 SF15 IAC Santa Elisa BRS Ponta Negra and Volumax and three temperatures T1 20 0-26 0-33 0 C T2 24 8-30 8-37 8 C T3 27 8-33 8-40 8 C with four replications of ten seeds The following aspects were evaluated emergence percentage emergence speed index average emergence speed average emergence time length fresh and dry mass of seedlings The temperature x cultivar interaction was not significant for emergence dry mass or length of sorghum seedlings The speed index and the mean emergence velocity increased in the regime of 27 9-34 3-40 8 C with means of 2 85 and 0 34 seeds days -1 respectively The responses regarding the cultivars were different for the growth and emergence variables The temperature regime of 24 8-30 8-37 8 C provided greater seedling development with higher seedling length fresh and dry mass values From the results it appears that the increase of 4 8 C in air temperature favors the emergence and initial growth of sorghum seedlings